Anti-inflammatory activity of the Methanol Extracts of Cissus Populnea GUILLS & PERS and Cissus Arguta HOOK. F. (2022)
Inflammation, characterized by pain, heat, swelling, redness, and loss of body function, is a living tissue's initial response to injury. There are ethno-botanical claims made about these plants for their wound-healing abilities which have not been scientifically validated. Therefore, this study was conducted to examine the anti-inflammatory activity of the two related Cissus species. The plant samples (leaf, stem and root) were dried, powdered and extracted with methanol (100%) and concentrated in vacuo and evaporated to dryness at room temperature. The anti-inflammatory activity of the plant extracts was evaluated using the in vitro protein denaturation and carrageenan-induced foot pad assay in chick, Diclofenac sodium as the reference and saline as control. Anti-inflammatory effects were observed in a dose-dependent manner. The phytochemical screening performed on the extracts showed the presence of phenols, flavonoids, tannin, anthraquinone, glycosides, saponin and alkaloid. The leaf extract of C. arguta and the stem extract of C. populnea inhibited protein denaturation with a value of 64.46±0.10 and 53.34±0.04 at 3 mg/mL respectively compared to the control group and diclofenac (52.86±0.00) at 3 mg/mL. All concentrations of extract tested; 10, 30, 100 mg/kg) for in vivo study had a significant effect in reducing total edema (AUC) (P < 0.01), and in most case they performed better than diclofenac. However, root extracts of C. populnea at 30 mg/kg (7.13±1.06) had better result in inhibiting edema in chicks than C. arguta extracts at 30 mg/kg (5.64±0.05). The plants exhibited anti-inflammatory activity which can be of great pharmacological importance.